(untitled) (International journal of artificial intelligence, 2024)
In the process of research, the peculiarities of teaching geography are analyzed using modern methods. The methodology of teaching geography as a pedagogical subject is inextricably linked with didactics. Geography teaching methodology based on the peculiarities of school geography, theoretical and practical problems of the content, forms, methods and means of education and upbringing were developed. Geography teaching methodology is closely related to pedagogy and psychology, since it is based on the age characteristics of students. It is necessary to cover ways to turn students from geography lessons into subjects of a full-fledged educational process.